Pengetahuan Ibu Pasca Bersalin tentang Kontrasepsi Metode Jangka Panjang (MKJP) di Wilayah Puskesmas Buaran Kota Pekalongan - Hilda Prajayanti; Putri Andanawarih (Akademi Analis Kesehatan Pekalongan, 2024)
Family planning according to WHO (World Health Organization) is an action that helps married couples to avoid unwanted pregnancies, get the birth they want, regulate the interval between pregnancies, control the time of birth in relation to the age of the husband and wife and determine the number of children in the family . The long-term contraceptive method (MKJP) is the most effective contraceptive method. But perhaps due to mothers' lack of knowledge regarding long-term contraception, including IUDs, mothers are afraid to choose long-term contraception, therefore almost on average in Indonesia, acceptors are dominated by users of short-term contraception such as injections, pills, condoms and so on. The research method is an analytical observational study with a cross sectional research design. The instrument used to obtain data is by using a structured interview method in the form of closed and open question questionnaires. It was concluded that almost all respondents before receiving health education about long-term contraceptive methods described a sufficient level of knowledge, 27 respondents (77.1%). All respondents after receiving health education about long-term contraceptive methods described an increased level of knowledge and most were knowledgeable. either 30 respondents (85.7%), the majority of respondents used MKJP as many as 14 respondents (46.7%), non-MKJP as many as 11 respondents (31.4%) and did not use family planning as many as 10 respondents (28.6%) , There were no respondents who experienced a decrease in their level of knowledge, 32 respondents experienced an increase, 14 respondents who had good knowledge used MKJP, 10 respondents used non-MKJP and 6 respondents did not use contraception, and respondents who had sufficient knowledge were 4 respondents who did not use contraception and 1 respondents use non MKJP.